Construction and performance of a silicon photomultiplier/extruded scintillator tail-catcher and muon-tracker - Adloff, Catherine; Eckert, Patrick; Kaplan, Alexander; Schultz-Coulon, Hans-Christian; Shen, Wei; Stamen, Rainer; Tadday, Klaus Alexander (Journal of Instrumentation, 2012)
A prototype module for an International Linear Collider (ILC) detector was built, installed, and tested between 2006 and 2009 at CERN and Fermilab as part of the CALICE test beam program, in order to study the possibilities of extending energy sampling behind a hadronic calorimeter and to study the possibilities of providing muon tracking. The “tail catcher/muon tracker” (TCMT) is composed of 320 extruded scintillator strips (dimensions 1000 × 50 × 5 mm 3 ) packaged in 16 one-meter square planes interleaved between steel plates. The scintillator strips were read out with wavelength shifting fibers and silicon photomultipliers. The planes were arranged with alternating horizontal and vertical strip orientations. Data were collected for muons and pions in the energy range 6 GeV to 80 GeV. Utilizing data taken in 2006, this paper describes the design and construction of the TCMT, performance characteristics, and a beam-based evaluation of the ability of the TCMT to improve hadronic energy resolution in a prototype ILC detector. For a typical configuration of an ILC detector with a coil situated outside a calorimeter system with a thickness of 5.5 nuclear interaction lengths, a TCMT would improve relative energy resolution by 6-16% for pions between 20 and 80 GeV.